Urban built form shapes avian richness in green spaces - Rogers, Morgan L. (Frontiers in Conservation Science, 2022)
Urban biodiversity plays an important role in ecological processes and ecosystem services within cities, making conservation a priority in many municipal sustainability plans. Urban green spaces (UGS) have been a key strategy for conservation by providing habitat for wildlife, including avian communities. While the ecological attributes necessary to enhance the habitability of UGS for avian communities are relatively well known, an understanding of how variation in the surrounding urban matrix influences avian richness outcomes in these spaces, is less understood. As new urban areas continue to develop and UGS become increasingly important habitat areas, urban designers and planners will need a better understanding of the ways in which urban built form patterns at the matrix-level influence avian biodiversity outcomes at the site-level in UGS. To that end, this study investigates the influence of 4 urban built form matrix-level variables and 6 UGS site-level variables on total avian richness and avian richness by foraging guild using generalized linear model methods in 22 UGS. This analysis was conducted using high resolution land cover data, building LiDAR data, and twenty years of bird occurrence data from the eBird community science program in well-surveyed UGS in Los Angeles, California. Several urban built form variables were found to improve model prediction for Carnivores, Insectivores, and Omnivore foraging guilds, but were not strong predictors of richness patterns on their own. The size of the UGS was the best predictor of richness patterns across all groups, confirming previous findings. The results of this study suggest that the most important factor in avian richness in UGS is the size of the area, but that urban built form plays a role too and improves avian richness model prediction.